A la recherche de la modernité démocratique occidentale au Proche-Orient .......... 201 - Skaff, Carole (Pensées orientale et occidentale : influences et complémentarité II, 2021)
IN SEARCH OF WESTERN DEMOCRATIC MODERNITY IN THE MIDDLE EASTIn the current context, political scenarios are diversifying. The events of the past few years have shown the influence of the West on some Middle Eastern countries as regards democratization. This situation, with all its politico-economic complexities, prompted one to wonder about one of the important paradigms of democracy: freedom. It seems that the practice of democracy has contradictory actions and characters. Currently, wars and especially those in the East are waged in the name of democracy, whose dissemination is carried out by formidable actors (army, militia, small seditious groups, etc.) and highly contestable methods (weapons, coercion, manipulation...). The distinction between friends and enemies turns out to be difficult (Carl Schmitt). This destabilizes the national situation and people’s feeling of security because imposing democracy by force is an undemocratic act, which hinders the political order and is only a mediation of domination (Max Weber). The East is probably not predisposed to follow western democratic modernity, to develop another ideology, to assert itself in a new state of mind (see Tocqueville) and to make a peremptory political choice. To democratize the East requires education, a profound and “revolutionary” evolution in the mentality, a process of radical change which must be based on a political, economic and intellectual development by the principles of freedom, of “equalization of conditions” (equal rights and consideration, see Tocqueville). These principles are essential for a true integration of the East into the Western community. And one wonders if one can evoke a “limited democracy” (see Rosanvallon) or a democracy that only concerns Western countries and leaders. Democratization may not be universalizable, particularly in some countries of the Middle East. Democratic modernity could emerge in the East from internal political reasons and practices without external intervention. It requires institutions, appropriate systems, and, of course - democrats. We will consider the issue, with great respect, in some countries, more westernized or less westernized, of the Middle East: Syria, Lebanon, Iraq, Yemen, where conditions are difficult as long as some countries manipulate the paradigms of democracy according to their goodwill and their logic. We will also examine the question of Western progress that influences the East intellectually and socio-culturally, and that of Western powers who sometimes seek to deal with problems, in certain aspects, through political instrumentalization that favors social drift and fragmentation (of family, religion, caste, ethnicity, etc.) to the detriment of the nation and civil society. Globalization only serves to comfort the West in its hegemony in the areas of the East of their great political, economic and strategic interests. According to Gérard Dussouy, in his Theories of Globality, “Globality is a total social fact. It is the result of the progress of communications and the globalization of capitalism.”